Analisis Potensi Pengembangan Pos Kesehatan Pesantren di Kota Medan - Purnama, Tri Bayu; Pertiwi, Arbitra Morlinda Rua (Faculty of Health Sciences, Syarif Hidayatullah State Islamic University of Jakarta, 2021)
The degree of public health in Islamic boarding schools is still a problem. Limited information about the Pesantren Health Posts as health services in the Pesantren will hamper the improvement of the community's health status in the Pesantren. This study used a qualitative method with a case study design conducted at the Boarding School with the boarding system in Medan from October to December 2019. Research informants of 2 people in each Pesantren were purposive sampling with in-depth interviews and observation using interview guidelines and observation guidelines. Information is analyzed with content analysis and data presentation in the form of matrix tables and descriptive narratives. Based on the results of the study, Islamic Boarding Schools in Medan City still do not have Poskestren. Terminology Poskestren more commonly known as the UKS (School Health Unit), and the Santri and Community Medical Center (BPSM). However, based on Poskestren input indicators, Islamic boarding schools in Medan have great potential to be developed into Poskestren. The conclusion of the research is that there is no common perception about